The most problematic freshwater invasive species in South America, Limnoperna fortunei (Dunker, 1857), and its status after 30 years of invasion - de Lucía, Micaela (2022)
Limnoperna fortunei, a problematic freshwater invasive mussel in South America, was first detected in 1991 at Bagliardi Beach, Río de la Plata (Argentina). Since then, there has been a high increase in population density, reaching up to 150,000 ind. m−2. The distribution, density, individual sizes, and associated mollusk assemblages of L. fortunei were evaluated 30 years after its first detection. Seven sites along Río de la Plata River were sampled between 2018 and 2020. The highest density was recorded in the La Balandra Beach (above the stabilization value) and the lowest density in the Martín García Island (IMG—by its acronym in Spanish—, below the stabilization value). Two reproductive events were observed: late spring and late summer. Our results showed different sets of species associated with Limnoperna fortunei, with protected areas such as the IMG standing out, showing greater species richness, including first records, versus other coastal environments. We recommend increasing conservation efforts given the constant advance of urbanization in the coastal sites of the province of Buenos Aires, with environmental impact studies prior to coastal reforms, and implementation of density control strategies for Limnoperna fortunei in protected areas.